Pengaruh Inovasi Konsumen Terhadap Niat Beli Mobil Wuling Melalui Proses Pembelajaran dan Nilai Manfaat yang Dimoderasi dengan Harga - Hamidah Hamidah; Puspita Chairun Nisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the influence of consumer innovation on the intention to buy Wuling cars in Jabodetabek through a learning process and value moderated by price. Therefore, the aim of this research is to develop the relationship between consumer innovation (CI), purchase intention (PI), learning process (LP) and value-benefit (PV) for wuiling brand cars in a collective society like Indonesia. It also investigates their relationship to price (P). This type of research is quantitative. The population in this study were wuiling car users in the Greater Jakarta area with an age range of 17-55 years of 182 respondents. Data collection was carried out in March-June 2022. The distribution of questionnaires was carried out online via the Google form with the scale used, namely a 5-point Likert scale which varies from Strongly Disagree (1) to Strongly Agree (5). Hypothesis testing in this study uses a structural equation model (SEM) and uses Lisrel 8.8 software. Based on the analysis it was concluded that not all variables have a positive effect on each other. The consumer innovation variable does not have a positive effect on the purchase intention variable, the consumer innovation variable affects the learning process variable, the learning process variable does not affect the purchase intention variable, the learning process variable influences the benefit value variable, the consumer innovation variable does not affect the benefit value variable, the benefit value variable affects the variable purchase intention, benefit value variable does not mediate consumer innovation variable to purchase intention variable, learning process variable does not mediate consumer innovation variable and purchase intention variable, benefit value variable does not mediate learning process variable and purchase intention variable, learning process variable and benefit value does not mediate the innovation variable and the purchase intention variable, the price variable managed to moderate the benefit value variable and the purchase intention variable. The findings in this study are that consumer innovation in Indonesia is still small, so that the intention to buy Wuiling brand car products has also decreased, which is caused by consumers not studying and understanding the advantages and value benefits of Wuiling brand cars, especially during the COVID-19 pandemic when In this case, the majority of consumers are more focused on basic needs than other needs. Then, during the COVID-19 pandemic, research respondents paid close attention to the price of a product or service because of the financial crisis during this pandemic.